THE ROLE OF SERGEI DOVLAMOV IN MODERN AMERICAN IMMIGRATION LITERATURE (Web of Discoveries: Journal of Analysis and Inventions, 2023)
This article focused on the russian and American literature writer Sergei Dovlatov, who has his place and style in modern American immigration literature, and his style.